Overview of reptiles breed as pet in two minicipalities of Recôncavo Baiano in the Northeast region of Brazil (Research, Society and Development, 2022)
The reptile breed is an practice can be harmful to the local biodiversity, as it can favor the capture of individuals from nature or the introduction of exotic species. This study aimed to assess the current scenario of breeding reptiles as pets in two municipalities in the Recôncavo Baiano region. For this, we identified the main species used, the social profile of the breeders, main motivators, and the breeders' perception regarding this practice. The data was obtained through semi-structured questionnaires, interviews, and conversations. A rarefaction curve and richness estimators were used to verify the sampling efficiency, while the Mann-Whitney and Kruskal-Wallis tests were used to verify the existence of differences within the interviewed. The Use-Value index (UV) was used to identify the most bred species. A total of 20 breeders who bred 120 pets belonging to 23 species and some hybrid individuals, 10 native and 13 exotics, were interviewed. There was a significant difference only in the number of residents per household. The richness estimators indicated the existence of five to 12 non-sampled species. Pantherophis guttatus was the species with the highest UV. The main motivation for breeding a reptile was the contact with other breeders, and these animals were obtained mainly through purchase. Our data reveal that the primary source of origin of these organisms is the reproduction in a captive environment. However, there is evidence of reptile capture from the natural environment. In addition, men between 20 and 40 years old were the main breeders and snakes were the animals of greatest interest.